UPAYA MENINGKATKAN HASIL BELAJAR LARI SPRINT MELALUI PENERAPAN GAYA MENGAJAR INKLUSI PADA SISWA KELAS V SD NEGERI 106153 KELAMBIR LIMA KECAMATAN HAMPARAN PERAK T.A 2017/2018 - Satria Suriadi (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
This research was conducted in August 2017 The recipients of the action in this study were all fifth grade students of SD Negeri 106153 Kelambir Lima, Hamparan Perak District, Deli Serdang Regency T. A. 2017/2018, totaling 45 students. Meanwhile, 3 students (6.66%) have not achieved complete learning with an average value of 80.74 student learning outcomes. Thus, it can be said that through the application of the inclusive teaching style applied by ending in cycle II, the results of learning to run sprints in athletic learning that were previously low have increased. The conclusion is "There is an increase in Sprint Running Learning Outcomes through the Application of Inclusive Teaching Style in Class V SD Negeri 106153 Kelambir Lima, Hamparan Perak District T. A. 2017/2018.